Plants of the Rocky Mountains / Linda Kershaw, Andy MacKinnon, Jim Pojar. - Kershaw, Linda, 1951- (Lone Pine Pub., 1998)
Easy to use identification guide to 1362 plants. Includes native uses of plants, habitat and ecology, similar species, name origins, and wildflower photo chart. 900 colour photos and 700 line drawings.